PROFIL KOMPETENSI LITERASI SAINS SISWA SMP SE-KECAMATAN PAGELARAN - Ana Rianti; Tri Jalmo; Berti Yolida (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2016)
The purpose of this research was  to know the competence of scientific literacy of class IX students. This research design was descriptive which used purposive sampling technique with 34 students. The result were quantitative data that were obtained from the score of PISA 2006 test and analyzed by calculating the average score. The qualitative data were obtained from internal dan exsternal factors that were analyzed by calculating the percentage score. The data analysis showed that students competence of scientific literacy were “very low” with mean score 33,60. The students of public school had higher competence of  scientific literacy than students in private school and  female students competence of scientific literacy was higher than  male students. Internal factor that influenced was students interest to continue their study. External factors that influenced were learning process in the class, science learning facilities, education background of parents, parents guidance at home, and teacher professionalism. Penelitian ini bertujuan untuk mengetahui kompetensi literasi sains siswa kelas IX SMP se- Kecamatan Pagelaran. Desain penelitian ini ialah deskriptif menggunakan teknik purposive sampling dengan sampel 341 siswa kelas IX. Data kuantitatif diperoleh dari skor uji tes soal PISA 2006 dan dianalisis dengan melakukan perhitungan rerata skor. Data kualitatif berupa faktor internal dan eksternal yang dianalisis dengan menghitung persentase skor.  Hasil analisis menunjukkan bahwa kompetensi literasi sains siswa termasuk dalam kriteria “sangat rendah” dengan skor rerata 33,60. Siswa sekolah  negeri memiliki kompetensi literasi lebih tinggi dibandingkan siswa sekolah swasta dan siswa perempuan memiliki kompetensi literasi lebih tinggi dibandingkan siswa laki-laki. Faktor internal yang berpengaruh adalah  minat siswa untuk melanjutkan sekolah. Faktor eksternal yang mempengaruhi adalah  proses pembelajaran guru dikelas, fasilitas pembelajaran IPA, latar belakang pendidikan orang tua, bimbingan orang tua dirumah, dan  profesionalisme guru.  Kata kunci : gender, literasi sains, status sekolah